(untitled) (Interdisciplinary Studies Journal, 2026)
This article aims to highlight how the educator’s personality impacts the training of students in the initial stages of teacher education. It is a reflective study that revisited the final evaluations of the students, who reflected on their formative paths and spontaneously brought up elements indicating the importance of considering the educator’s personality in the educational act. This study is based on the Ontopsychological pedagogy approach, which understands the human being in both their conscious and unconscious dimensions and, with its three discoveries (semantic field, Ontic In-Self, and deflection monitor), promotes a new educational perspective for teaching professionals in training processes. The learners highlight elements that demonstrate the need to consider the educator’s personality, as they are the ones who manage the teaching-learning relationships based on who they are as a person. Another important contribution pointed out by the study is that this formative dimension, although not a direct focus of training in university courses, should be considered as fundamental, and educators should seek self-knowledge in order to improve their educational relationships with their learners.